Enhancing Digital Competencies through Technology-Enhanced Learning among Students at MI Nurul Huda Bengkulu - Widiarty; Johanes Sapri; Nesna Agustriana (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2026)
The rapid advancement of digital technology has transformed educational practices and increasingly necessitates the development of students’ digital competencies from an early stage of education. This study investigates the role of Technology-Enhanced Learning (TEL) in enhancing digital competencies among students at MI Nurul Huda. The study is grounded in the assumption that the meaningful integration of technology into learning activities can foster not only students’ technical proficiency but also their ability to access, evaluate, create, and communicate information effectively and responsibly. Employing a qualitative descriptive approach, this study explores the implementation of technology-enhanced learning, students’ engagement with digital learning resources, and the development of their digital competencies through classroom observations, interviews, and relevant documentation. The findings indicate that the integration of digital technologies into learning activities contributes positively to students’ digital competencies, particularly in terms of basic technology operation, information access, digital communication, collaborative learning, and responsible use of digital resources. Nevertheless, the effectiveness of TEL is influenced by several factors, including teachers’ digital competence, the availability of technological infrastructure, students’ varying levels of digital literacy, and the need for appropriate pedagogical guidance. The study concludes that Technology-Enhanced Learning can serve as an effective pedagogical approach for strengthening students’ digital competencies when technology is integrated purposefully within a supportive learning environment. These findings highlight the importance of continuous teacher development, adequate technological resources, and contextually relevant digital learning strategies to ensure the sustainable development of digital competencies among students at the elementary madrasah level.